2013
DOI: 10.1186/1743-422x-10-175
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of tumor-suppressive microRNAs silenced by DNA hypermethylation in cervical cancer

Abstract: BackgroundMultiple studies proved that miRNAs have a causal role in tumorigenesis. Some miRNAs are regulated by epigenetic alterations in their promoter regions and can be activated by chromatin- modifying drugs.MethodsWe treated cervical cancer cells with 5-aza-2’-deoxycytidine and get a microarray analysis. Dysregulation of miRNAs was measured by qPCR in cervical cell lines and methylation status of them in cervical cancer tissue were performed with MeDIP-qPCR assay.ResultsWe found hypermethylation of miR-43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 27 publications
0
45
0
1
Order By: Relevance
“…Li et al () revealed that knockdown of miR‐641 inhibited the proliferation, migration, and invasion of ovarian cancer cells by regulating the p63/miR200 axis. The previous study showed an increased expression of miR‐641 in CC (Yao et al, ) but the effects of miR‐641 dysregulation in CC was unclear. In this study, we found that miR‐641 expression was significantly increased in CC tissues, and knockdown of miR‐641 could inhibit the invasion and migration of CC cells.…”
Section: Discussionmentioning
confidence: 95%
“…Li et al () revealed that knockdown of miR‐641 inhibited the proliferation, migration, and invasion of ovarian cancer cells by regulating the p63/miR200 axis. The previous study showed an increased expression of miR‐641 in CC (Yao et al, ) but the effects of miR‐641 dysregulation in CC was unclear. In this study, we found that miR‐641 expression was significantly increased in CC tissues, and knockdown of miR‐641 could inhibit the invasion and migration of CC cells.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, a study found that miRNA pairs could predict which lesions would progress to SCCC. Recent work in the miRNA field has focused on epigenetic changes that affect miRNA expression in the progression of CIN to invasive disease using human tissue samples and treated in vitro cultures [125]. Importantly, one of the miRNAs that was found to be regulated by methylation and important for higher grade lesion, miR-124 [123], has been under testing for a quantitative methylation-specific PCR assay on Pap specimens [124].…”
Section: The Role Of Mirnas In Initiating Lesions To Squamous-cell Cementioning
confidence: 99%
“…in cervical cancers has been linked to increased promoter methylation of respective genes 73,74,83,84 . These data are fully in line with the concept that an increase in specific genetic and epigenetic alterations reflects a longer duration of existence of the underlying lesion.…”
Section: Mir-124-2 Hsa-mir-124-3 Hsa-mir-149 Hsa-mir-203 Hsa-mir-mentioning
confidence: 99%